2001
DOI: 10.1016/s0960-9822(01)00268-8
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast Clp1p phosphatase regulates G2/M transition and coordination of cytokinesis with cell cycle progression

Abstract: S. pombe Clp1p affects cell cycle progression in a markedly different manner than its S. cerevisiae homolog, Cdc14p. This finding raises the possibility that related phosphatases in animal cells will prove to have important roles in coordinating the onset of cytokinesis with the events of mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
295
0
29

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(331 citation statements)
references
References 33 publications
7
295
0
29
Order By: Relevance
“…Previous studies have shown that structural defects in the actomyosin ring are monitored via a checkpoint mechanism that involves the protein phosphatase Clp1p/Flp1p and the SIN (Le Goff et al, 1999;Liu et al, 1999Liu et al, , 2000Cueille et al, 2001;Trautmann et al, 2001;Mishra et al, 2004). We have shown that clp1⌬ displays an additive deleterious effect in combination with pdk1⌬, consistent with the idea that pdk1⌬ cells assemble structurally defective rings and that their maximal viability depends on Clp1p function.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that structural defects in the actomyosin ring are monitored via a checkpoint mechanism that involves the protein phosphatase Clp1p/Flp1p and the SIN (Le Goff et al, 1999;Liu et al, 1999Liu et al, , 2000Cueille et al, 2001;Trautmann et al, 2001;Mishra et al, 2004). We have shown that clp1⌬ displays an additive deleterious effect in combination with pdk1⌬, consistent with the idea that pdk1⌬ cells assemble structurally defective rings and that their maximal viability depends on Clp1p function.…”
Section: Discussionsupporting
confidence: 88%
“…This could result from improper assembly/function of the actomyosin ring or from defective SIN signaling. Mishra et al (2004) recently reported that a checkpoint mechanism that depends on the protein phosphatase Clp1p/Flp1p (Cueille et al, 2001;Trautmann et al, 2001), and SIN allows for completion of cytokinesis and increased viability in response to minor damage to the cell division apparatus. Several viable mutants partially defective in the cell division apparatus depend on Clp1p for their viability.…”
mentioning
confidence: 99%
“…However, this phosphomutant cannot induce the assembly of full contractile rings [Roberts-Galbraith et al, 2010]. Another interesting point is that Cdc15 dephosphorylation is partly dependent on the phosphatase Clp1, a known effector of the SIN pathway [Cueille et al, 2001;Trautmann et al, 2001;Chen et al, 2008]. Clp1 localization at the contractile ring depends on Mid1 (see Fig.…”
Section: Mechanisms Of Contractile Ring Assemblymentioning
confidence: 99%
“…elegans and Homo sapiens on the basis of sequence similarity to the budding yeast Saccharomyces cerevisiae protein (Li et al, 1997;Cueille et al, 2001;Trautmann et al, 2001;Gruneberg et al, 2002). (All) Cdc14 proteins characterised to date are dual-specificity protein phosphatases that share a core of approximately 300 amino acids towards the amino terminus that includes a strictly conserved protein-phosphatase domain motif (Gray et al, 2003).…”
mentioning
confidence: 99%